1997
DOI: 10.1021/jf970036j
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Nutritive Potential and Toxic Constituents of Different Provenances of Jatropha curcas

Abstract: Eighteen different provenances of Jatropha curcas from countries in West and East Africa, North and Central America, and Asia were characterized for nutrient and antinutritional factors. The mean weight of the 18 seed provenances was 0.64 ± 0.10 g (mean ± sd). The kernel forms a large proportion of the seed and accounts for 61.3% ± 3.1%. There were large variations in the contents of CP (19−31%; 26.0% ± 3.2%), lipid (43−59%; 53.0% ± 4.8%), neutral detergent fiber (3.5−6.1%; 5.0% ± 0.87%), and ash (3.4−5.0%; 4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
330
5
21

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 405 publications
(369 citation statements)
references
References 21 publications
13
330
5
21
Order By: Relevance
“…Each fruit contains 2-3 oblong black seeds which can produce oil. The seed kernel oil contained 40-60 % (w/ w) oil (Makkar et al, 1997). The seed oil extracted is found useful in medicinal and veterinary purpose, as insecticide, for soap production and as fuel substitute (Gubitz et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Each fruit contains 2-3 oblong black seeds which can produce oil. The seed kernel oil contained 40-60 % (w/ w) oil (Makkar et al, 1997). The seed oil extracted is found useful in medicinal and veterinary purpose, as insecticide, for soap production and as fuel substitute (Gubitz et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The seeds of most known J. curcas accessions are highly toxic, including the African accessions, due to the presence of cursive ingredients such as curcin and phorbol esters [63,64]. Yet, the current study demonstrated that J. curcas can be dispersed and eaten by small mammals.…”
Section: Discussionmentioning
confidence: 58%
“…In relation to bioactive molecules analyzed in DJCM (Table 2), phorbol esters content (0.06 mg/g) is lower than that found for Makkar et al (1997), who evaluated the content of these in nontoxic to the animals varieties (0.11 mg/g), by Rakshit et al (2008) evaluating DJCM in diet for rats (0.2 mg/g). Chivandi et al (2006), evaluating the effect of different methods of detoxification in the Jatropha curcas meal with 0.8 mg/g of phorbol esters, observed significant losses in pigs blood parameters.…”
Section: Resultsmentioning
confidence: 85%
“…The concentrations of phorbol esters were analyzed following the method by Makkar et al (1997), the contents of total phenols and total tannins analyzed by Folin-Ciocalteu, condensed tannins (proanthocyanidins) by the butanol-HCl method (Makkar, 2000) and the concentration of saponins analyzed according to Makkar et al (2007).…”
Section: Chemical Analysesmentioning
confidence: 99%